Optimizing Project Delivery in Educational Infrastructure: The Impact of Fast-Track Methods in Indonesian School Construction - Jayady, Arman; Tua Rajagukguk, Sahala (International Journal Labs, 2024)
Infrastructure development is essential for socio-economic growth, especially in the field of education, where facilities directly contribute to the development of human resources. In areas such as Sorong City, where the Indonesian government has invested a lot of funds, efficient project execution has become very important due to tight deadlines and budget constraints. This study examines the application of the fast-track method in managing the Model X School Construction Project in Sorong, focusing on its impact in reducing the duration and cost of the project. The fast-track method, characterized by overlapping and compression of activities, used in conjunction with Microsoft Project, represents a shift from the traditional, sequential project delivery model. The findings of this study show that the application of the fast-track method can reduce the project duration by 17 days and save indirect costs by 0.9%, or equivalent to IDR 13,073,000. These results confirm the effectiveness of this method in improving operational efficiency and reducing expenses in the context of projects that require quick and economical completion. This research contributes to the literature by providing insight into the practical benefits of fast-tracking methods in the construction industry, particularly educational infrastructure, and highlighting its potential for wider application to various types of construction projects.